PELANGGARAN HUKUM ADAT MINANGKABAU DALAM KABA ANGKU KAPALO SITALANG - Okto Arianto (Jurnal Elektronik WACANA ETNIK, 2010)
This thesis is a result of research on Kaba Angku Kapalo Sitalang by applying  sociology of literature. In Kaba Angku Kapalo Sitalang, there is a violation of Minangkabau custom law done by the people. The analysis focuses on the violation of Minangkabau custom law by emphasizing Undang Undang Nan Dua Puluh (The twenty rules). In this research, the writer explains the structural analysis by describing theme, characterization, background and plot. Furthermore, Sociology of literature is a branch of literary criticism in its reflective features. This research views literature as mirror of society. Thus, Literature can be a direct reflection of various violation of custom law in society. The writer uses qualitative method in doing this research. Based on this research, it can be concluded that the problem about crimes or any actions against the law of custom in Kaba Angku Kapalo Sitalang covers five criminal actions; samun saka (an action or behavior by disturbing social relation of others), kicuah kicang (deceiving), sumbang salah (the faults behavior), sia baka (making disorder in society such as creating social conflict), and tikam bunuh (murder). The social effect of the violation custom law in Kaba Angku Kapalo Sitalang; first, moral values and norms in society are fading, second, there is a social imbalance in society, and the third, the criminality is rising. In the end, the aim at living a safe, peaceful and prosperous society cannot be achieved.